Reef fish monitoring as a coral reef resilience indicator in the Sempu Strait, South of East Java, Indonesia - GATUT BINTORO; ANDIK ISDIANTO; NUDDIN HARAHAB; ANDI KURNIAWAN; AGUS DWI WICAKSONO; RELIA MAHARDITHA; AULIA LANUDIA FATHAH; BERLANIA MAHARDIKA PUTRI; MUCHAMAD FAIRUZ HAYKAL; MUHAMMAD ARIF ASADI; ARIEF SETYANTO; TRI DJOKO LELONO; OKTIYAS MUZAKY LUTHFI; DWI CANDRA PRATIWI (Society for Indonesian Biodiversity, 2023)
Abstract. Bintoro G, Isdianto A, Harahab N, Kurniawan A, Wicaksono AD, Maharditha R, Fathah AL, Putri BM, Haykal MF, Asadi MA, Setyanto A, Lelono TD, Luthfi OM, Pratiwi DC. 2023. Reef fish monitoring as a coral reef resilience indicator in the Sempu Strait, South of East Java, Indonesia. Biodiversitas 24: 4950-4959. Sempu Island is designated as a nature reserve which is surrounded by a fairly high diversity of coral reefs. Since the high activities of fishing ports near this island, the anthropogenic pressure seriously became a threat to the biodiversity of coral reefs in this nature reserve. Continuous observation of reef fish is an important activity to monitor the coral reef health condition. Since then, bimonthly monitoring using an underwater visual census has been conducted from October 2021 to May 2022. Based on these observations obtained that the average reef fish abundance was in the